The role of occupational safety measures on reducing accidents in marble quarries of Iscehisar region - Ersoy, Metin (elsevier, 2013)
Marble and natural stone mining is associated with the risk of various work accidents,since it is one of the heavy business lines of the industry. Today,there is asignificantprogress in reducing the work- related accidents as a result of the measures taken by work safety analysis.Occupational safety is impo r- tant, since it focuses on people and continuation of living quality of people in their remaining part of lives. For this purpose, the occupational accident statistics 10 of marble quarries in Afyonkarahisar Iscehisar region, where the oldest marble quarries of Anatolia are located have been investigated,and the both applied and ignored job safety measures were observed. Than accident and safety quarry indexes were calculated by using Analytic Hierarchy Process (AHP)method to determine the weight of the accident risks and the safety measures taken.Anegative exponential relationship (R2 = 0.8116)has been identified between accident index and the safety index in quarries.
Due to copyright restrictions, the access to the publisher version (published version) of this article is only available via subscription. You may click URI (with DOI: 10.1016/j.ssci.2013.03.005) and have access to the Publisher Version of this article through the publisher web site or online databases, if your Library or institution has subscription to the related journal or publication.
Keywords: Quarry management; Occupational safety.Work accident; Marble and natural stone